Insights Gained from Weather Extremes and Health Crises in Strengthening Mass Transit Durability - Jain, Anshul; Varma, Hridayesh (Transportation Development Research, 2026)
Mobility networks worldwide face escalating challenges from climate-induced environmental shifts and major disruptions such as the global COVID-19 pandemic. This scoping review investigates the resilience of public transport systems through a structured 4R framework—robustness (strength), redundancy (alternatives), resourcefulness (ingenuity), and rapidity (speed). The analysis draws on four diverse regional cases from Britain, Southern Africa, Central America, and North America to provide comparative insights. The article reveals that weather-related interruptions, including floods, storms, and extreme temperatures, predominantly expose structural weaknesses in infrastructure and place significant strain on administrative and operational capacities. In contrast, pandemic-related disruptions primarily test the adaptability and functional agility of transport services, highlighting the need for flexible operational models and rapid response capabilities. Key findings underscore the critical role of effective early warning and alert mechanisms in mitigating risks. Sustained investment in resilient infrastructure has proven valuable, as demonstrated by proactive approaches in Britain and Central America. Conversely, chronic under-maintenance and funding shortages have severely undermined system performance, particularly in Southern Africa. The study proposes practical strategies to enhance resilience, emphasizing the development of integrated and diversified mobility networks that combine public transport with active and shared modes. It also stresses the importance of strengthening inter-agency collaboration, governance structures, and preparedness planning to better equip transport systems for futur uncertainties.